Application of Polyacrylamide (PAM) through Lay‐Flat Polyethylene Tubing: Effects on Infiltration, Erosion, N and P Transport, and Corn Yield. Issue 4 (1st July 2017) - McNeal, J. P.; Krutz, L. J.; Locke, M. A.; Kenty, M. M.; Atwill, R. L.; Pickelmann, D. M.; Bryant, C. J.; Wood, C. W.; Golden, B. R.; Cox, M. S.
Abstract : Polyacrylamides (PAMs), when applied as a soil amendment, purportedly improve soil infiltration, decrease erosion, and reduce offsite agrochemical transport. The effect of PAM on infiltration, erosion, agrochemical transport, and crop yield when applied in furrow to mid‐southern US production systems has not been evaluated. The objective of this study was to assess PAM effects on infiltration, erosion, corn ( Zea mays L.) grain yield, and nitrogen (N) and phosphorus (P) transport when applied at 10 mg L −1 through lay‐flat polyethylene tubing. A 2‐yr field study was conducted at the Mississippi State Delta Research and Extension Center in Stoneville, MS, on a Dundee silt loam and a Forestdale silty clay loam. The experimental design was a randomized complete block with four replications of each treatment: irrigated plus no PAM (control) and irrigated plus PAM at 10 mg L −1 . Each irrigation event delivered 102 mm of water at 18.9 L m −1 per furrow, and runoff was captured in a holding tank on the lower end of each plot. Pooled over year and soil texture, PAM increased infiltration and corn grain yield by 6% ( P ≤ 0.0398). Polyacrylamide effects on the offsite transport of sediment and N and P were inconsistent, varying across year and soil texture. Results indicate that PAM improves infiltration and corn grain yield on silt loam and silty clay loam textured soils; however, further research is required before PAM can be recommended as a best management practice for mitigating erosion and offsite agrochemical transport in mid‐southern production systems. Core Ideas: Polyacrylamide applied in furrow improves soil infiltration. Polyacrylamide applied in furrow has minimal effect on erosion and nutrient transport. Polyacrylamide applied in furrow improves corn yield.